Language innovation on social media: a case study of rizz on TikTok - Noraishah Gulnazir; Siti Zaidah Zainuddin (Penerbit Universiti Kebangsaan Malaysia, 2025)
The English language is in a constant state of evolution, particularly with the influence of online platforms. Each year, new words and expressions emerge, highlighted by the Oxford Dictionary’s Word of the Year (WOTY) announcement. In 2023, rizz, a term popularised on TikTok, which means the ability to woo someone, was named WOTY. Given the rapid rise of rizz from being a novel word to gaining widespread recognition, this study examines the invention and proliferation of this word using a mixed-method approach. With the aid of Diffusion of Innovations theory, 100 TikTok videos were analysed for their content and the English Trends corpus analysis was utilised, along with the tool Google Trends to understand the spread of this lexical item. The results show that rizz began to be used in 2022, and its usage has slowly declined since it was named WOTY. It was also found that creativity and virality are some of the pertinent aspects of word dissemination on TikTok. Aside from that, American English continues to dominate a newer platform like TikTok, as it has with previous applications. This dominance is evident in the widespread use of American slang and expressions which often become global trends. The study emphasizes the concept of language mobility on social media by showing how new lexical items are created online and reach a global audience, potentially becoming dictionary entries. The invention of novel lexical items is expected to continue in the future as it demonstrates the ongoing change and variation of the English language in a fast-paced world.